2015
DOI: 10.1007/s11249-015-0536-z
|View full text |Cite
|
Sign up to set email alerts
|

On a Model for the Prediction of the Friction Coefficient in Mixed Lubrication Based on a Load-Sharing Concept with Measured Surface Roughness

Abstract: A new model was developed for the simulation of the friction coefficient in lubricated sliding line contacts. A half-space-based contact algorithm was linked with a numerical elasto-hydrodynamic lubrication solver using the load-sharing concept. The model was compared with an existing asperity-based friction model for a set of theoretical simulations. Depending on the load and surface roughness, the difference in friction varied up to 32 %. The numerical lubrication model makes it possible to also calculate li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…To simulate contact of two opposing surfaces resulting from lithostatic pressure in Geo‐energy reservoirs (represented by σ 3 ′ in the experiments), a half space‐based, dry contact model from Tribonet was used (Akchurin et al, 2015; Lubrecht & Ioannides, 1991; Tribonet n.d.). The model uses the artificially generated surfaces discretized to either 2,048 × 682 (for model calibration) or 768 × 256 nodes (for parametric analysis).…”
Section: Numerical Modeling Of Fracture Transmissivity (Under Normal mentioning
confidence: 99%
“…To simulate contact of two opposing surfaces resulting from lithostatic pressure in Geo‐energy reservoirs (represented by σ 3 ′ in the experiments), a half space‐based, dry contact model from Tribonet was used (Akchurin et al, 2015; Lubrecht & Ioannides, 1991; Tribonet n.d.). The model uses the artificially generated surfaces discretized to either 2,048 × 682 (for model calibration) or 768 × 256 nodes (for parametric analysis).…”
Section: Numerical Modeling Of Fracture Transmissivity (Under Normal mentioning
confidence: 99%
“…Spikes presented the basics of elastohydrodynamic lubrication and its practical applications. Previously, a number of studies have been reported to model the EHL/mixed‐EHL regime in concentrated contacts under rolling/sliding conditions . In those papers, a load‐sharing concept originally developed by Johnson et al was employed, and a variation of the friction coefficient was shown for the various experimental conditions (very high to low load, the effect of surface roughness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the separation distance h s has the same shape as the film thickness h but with a constant offset ε so that volume conservation is preserved (see Akchurin et al. 30 for more details), as can be inferred from Figure 3. The offset ε is obtained iteratively in the asperity contact model, by satisfying the following equation where A is the total area and A is the lubricated area.…”
Section: Mathematical Model: Mixed Lubricationmentioning
confidence: 95%
“…In fact, for the normal contact pressures p a calculation the elastic-perfectly plastic contact model of Akchurin et al 30 is employed. For the tangential contact problem, the model of Bazrafshan et al 31 is employed.…”
Section: Asperity Contact Componentmentioning
confidence: 99%